(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the issues of transforming the state border security system in the modern geopolitical context. The possibilities of applying artificial intelligence (AI), autonomous sensor networks, and tactical modeling methods in the operational command and control echelons of border troops are scientifically and theoretically substantiated. Furthermore, the prospects for implementing intellectual platforms in the state border protection system of the Republic of Uzbekistan are examined.